HUBUNGAN ANTARA KEPATUHAN DIET DENGAN KADAR GULA DARAH PENDERITA DM TIPE 2 PUSKESMAS TRAUMA CENTER SAMARINDA - Muhammad Taufiq Zul Fahmi; Siti Khoiroh Muflihatain; Nur Fithriyanti Imamah (2023)
Diabetes mellitus is a chronic disease with metabolism disorders that cause insulin insufficiency. Dietary compliance is a factor that affects blood sugar levels in people with diabetes mellitus. So, someone with good dietary compliance will have good who blood glucose and if someone who doesn’t adhere to dietary will have bad blood glucose levels. The purpose of this study was to determine the relationship between dietary compliance and blood sugar levels of people with type 2 diabetes mellitus in the work area of the Trauma Center Health Center, Samarinda City. The design of this research is descriptive correlational. The research sample was 190 people. Data were obtained using the Perceived Dietary Adherence Questionnaire (PDAQ) questionnaire for dietary compliance variables and the Easy Touch blood sugar tool for blood sugar levels. Bivariate test used chi square test. From the statistical test results, it was found that there was a significant p-value of 0.014 <α (0.05) then Ha is accepted, indicating that there was a significant relationship between dietary adherence and blood sugar levels in people with type 2 diabetes mellitus of the Trauma Center Health Center, Samarinda City. The suggestion is people with diabetes mellitus are advised to follow and maintain a diet pattern so that blood sugar levels can be controlled properly, and can improve their health patterns. Keywords: Diabetes Mellitus Type 2, Dietary Compliance, Blood Sugar Levels